2015
DOI: 10.1063/1.4927739
|View full text |Cite
|
Sign up to set email alerts
|

The influence of charge and magnetic order on polaron and acoustic phonon dynamics in LuFe2O4

Abstract: Femtosecond optical pump-probe spectroscopy is used to reveal the influence of charge and magnetic order on polaron dynamics and coherent acoustic phonon oscillations in single crystals of charge-ordered, ferrimagnetic LuFe2O4. We experimentally observed the influence of magnetic order on polaron dynamics. We also observed a correlation between charge order and the amplitude of the acoustic phonon oscillations, due to photoinduced changes in the lattice constant that originate from the photoexcited electrons. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Ultrafast spectroscopy is a powerful tool for studying structural dynamics in quantum materials through the generation of coherent phonon oscillations driven by femtosecond optical pulses [1][2][3][4]. The coherent excitation of acoustic phonons occurs when an intense femtosecond optical pump pulse launches a strain wave along the surface normal, resulting from, for example, thermoelastic, electron-phonon coupling, and piezoelectric effects that are driven by the photoexcitation of charge carriers [4][5][6][7][8][9]. This optically induced strain wave is then measured in the time domain via coherent oscillations in the reflectivity or transmission of an additional optical probe pulse, when the probe penetrates deeper than the acoustic wavelength.…”
mentioning
confidence: 99%
“…Ultrafast spectroscopy is a powerful tool for studying structural dynamics in quantum materials through the generation of coherent phonon oscillations driven by femtosecond optical pulses [1][2][3][4]. The coherent excitation of acoustic phonons occurs when an intense femtosecond optical pump pulse launches a strain wave along the surface normal, resulting from, for example, thermoelastic, electron-phonon coupling, and piezoelectric effects that are driven by the photoexcitation of charge carriers [4][5][6][7][8][9]. This optically induced strain wave is then measured in the time domain via coherent oscillations in the reflectivity or transmission of an additional optical probe pulse, when the probe penetrates deeper than the acoustic wavelength.…”
mentioning
confidence: 99%
“…Although previous Raman and infrared studies have shown lattice anomalies through the successive electronic and magnetic transitions, the intrinsic charge dynamics and its role on the magnetoelastic coupling remains unclear. Recently, Lee et al used ultrafast optical spectroscopy to show the influence of magnetic ordering on quantum charge fluctuations, which can govern the interplay between electric polarization and magnetism …”
mentioning
confidence: 99%